Flood-Irrigated Corn Silage Cost-Return Budget (Custom Harvested) - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn silage production.
MF581_1996_10
Keywords: MF581; Economics; Crops; MF